Preschool Education Management: Current Status And Prospects - Based On Modern Management Competences - Azizov, A’zam (International Conference on Global Trends and Innovations in Multidisciplinary Research, 2026)
This article examines the main aspects of educational quality management in the preschool education system and provides practical recommendations for ensuring the effectiveness of quality management. Special attention is also paid to management approaches aimed at improving educational outcomes, ensuring continuous development, and meeting modern social and educational requirements.